Boron-induced suppression of recrystallization during creep in FeNi-based superalloy - Cham Il Kim; Lee, Ji Yeong; Won Tae Kim; Eun Soo Park; Heon Kang; Do Hyang Kim (Elsevier BV, 2025)
This study investigates the effects of boron on microstructural evolution and creep properties in a FeNi-base superalloy, showing that boron plays a role in significant enhancement of the creep resistance by suppression of recrystallization during creep. Detailed analyses using transmission electron microscopy, atom probe tomography, and electron backscattered diffraction revealed that boron segregates at grain boundaries and at the interface between the matrix and the precipitate, thereby increasing grain boundary cohesion and suppressing dynamic recrystallization. Moreover, boron stabilizes the grain structure by increasing the recrystallization threshold, thus inhibiting recrystallization during creep. The effect of boron in strengthening the grain boundary is particularly pronounced in the creep test with lower strain rate, where it effectively extends the creep rupture life, while this effect is less emphasized in the high temperature tensile test with higher strain rate. These findings suggest that the addition of boron is crucial for the optimization of the high-temperature performance of FeNi-base superalloys.